Microwave interferometric radiometry in remote sensing: An invited historical review. Issue 6 (24th June 2014) - Martín‐Neira, M.; LeVine, D. M.; Kerr, Y.; Skou, N.; Peichl, M.; Camps, A.; Corbella, I.; Hallikainen, M.; Font, J.; Wu, J.; Mecklenburg, S.; Drusch, M.
Abstract The launch of the Soil Moisture and Ocean Salinity (SMOS) mission on 2 November 2009 marked a milestone in remote sensing for it was the first time a radiometer capable of acquiring wide field of view images at every single snapshot, a unique feature of the synthetic aperture technique, made it to space. The technology behind such an achievement was developed, thanks to the effort of a community of researchers and engineers in different groups around the world. It was only because of their joint work that SMOS finally became a reality. The fact that the European Space Agency, together with CNES (Centre National d'Etudes Spatiales) and CDTI (Centro para el Desarrollo Tecnológico e Industrial), managed to get the project through should be considered a merit and a reward for that entire community. This paper is an invited historical review that, within a very limited number of pages, tries to provide insight into some of the developments which, one way or another, are imprinted in the name of SMOS.